2022
DOI: 10.1186/s12891-022-05492-6
|View full text |Cite
|
Sign up to set email alerts
|

Primary care consultations and pain medicine prescriptions: a comparison between patients with and without chronic pain after total knee replacement

Abstract: Background Approximately 20% of patients experience chronic pain after total knee replacement (TKR). The impact of chronic pain after TKR on primary care services in the UK is currently unknown. The aim of this study was to compare primary care consultations and pain medicine prescriptions between patients with and without chronic pain after TKR. Methods Data from 5,055 patients who received TKR between 2009 and 2016 with anonymised linked data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Chronic postsurgical pain is typically defined as pain that develops after a surgical procedure and persists at least three months [5,6]. Chronic postsurgical pain is associated with lower patient satisfaction and higher societal and health care expenses due to resource-intensive revision surgery and long-term recovery [4,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic postsurgical pain is typically defined as pain that develops after a surgical procedure and persists at least three months [5,6]. Chronic postsurgical pain is associated with lower patient satisfaction and higher societal and health care expenses due to resource-intensive revision surgery and long-term recovery [4,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is possible for patients to experience ongoing or chronic pain related to the operated joint after orthopaedic surgery; for example, approximately up to 10% to 20% of patients’ experience is not satisfied after total knee arthroplasty (TKA) 49,50 . A portion of these patients may seek treatment of chronic pain after surgery through their primary care provider; this need for care emphasizes the importance of fluent communication among health care teams 49 . Persistent postoperative pain may lead to an increase in the consumption of opioid medications and long-term opioid dependence, which is not an uncommon postsurgical complication 51 .…”
Section: Team Approach: Role-specific Interventionmentioning
confidence: 99%
“…care providers, which may facilitate the integration of interdisciplinary care. Finally, it is possible for patients to experience ongoing or chronic pain related to the operated joint after orthopaedic surgery; for example, approximately up to 10% to 20% of patients' experience is not satisfied after total knee arthroplasty (TKA) 49,50 . A portion of these patients may seek treatment of chronic pain after surgery through their primary care provider; this need for care emphasizes the importance of fluent communication among health care teams 49 .…”
Section: Effect Of Opioids On Orthopaedic Patientsmentioning
confidence: 99%
“…The incidence of CPSP following TKA varies based on the cohort and sampling techniques applied, with most studies identifying a range of 15-25%, [3,4], though estimates have suggested as many as one in three persons experience ongoing pain following this type of surgery. Persistent pain negatively impacts several aspects of the patient experience, leading to higher healthcare costs and worse patient satisfaction [5], as well as functional disability and decreases in quality of life [6,7]. Chronic pain accounts for over $600 billion dollars annually, more than double that of heart disease and diabetes [1].…”
Section: Introductionmentioning
confidence: 99%